The Implementation of Technology Acceptance Model towards Mobile Photography Application Adobe Lightroom - Purnomo, Hari Setiawan (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
This research is entitled The Implementation Of Technology Acceptance Model Towards Mobile Photography Application Adobe Lightroom. The subjects in this research were Purwokerto Adobe Lightroom Mobile Photography App participants. Anyone who met and used the Adobe Lightroom Mobile Photography Application in Purwokerto. The data collection methodology applied in this study is a poll or questionnaire technique directly or through google form. Hypothesis testing uses PLS software called Smart PLS 3.0, hypothesis testing can also be done by looking at the results of the path coefficient or inner model which shows the t-statistic. The results of the t-test analysis it is known that the statistical t-value of the Perceived Usefulness variable on Attitude is 2.458 with a p-value of 0.014, and t-value of the Perceived Ease of Use variable on Attitude is 3,850 with a p-value of 0.000, t value of the Perceived Enjoyment variable on attitude is 3,800 with a p-value of 0.000, and a p-value of less than 0.05 with a positive direction, it can be concluded that perceived usefulness, perceived enjoyment, perceived ease of use has a positive effect on attitude, so the hypothesis research is accepted. Based on the t-test analysis, it is known that the statistical t-value of the attitude variable to Continuance Intention is 7,697 with a p-value of 0.000. with a positive direction, it can be concluded that attitude has a positive effect on Continuance Intention. This shows that the better the attitude, the higher the Continuance Intention, so the fourth hypothesis is accepted. The conclusion of research is perceived usefulness, Perceived ease of use, and perceived enjoyment have positive effect on user’s attitude towards Adobe Lightroom. Attitude has a positive effect on users' continuance intention to use Adobe Lightroom. Keyword : perceived usefulness, perceived enjoyment, perceived ease, attitude, continuance Intention